Domain of Property Value Determinants in Urban Areas - Artiani, Gita (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The construction industry has a strategic role in supporting the development of urban areas through the development of infrastructure, housing, and commercial space. However, rapid urbanization and the complexity of managing construction projects create challenges in determining optimal property value. Although many studies have been conducted on property values, studies specifically addressing the interaction between construction management and the determinants of property values in urban zones are still limited, especially in Indonesia. This study aims to identify and analyze various factors that affect property value from the construction management perspective through integrative literature studies. The analysis revealed 62 factors grouped into four main domains: types, causes, impacts, and solutions. Dominant factors such as land prices, transportation accessibility, and project sustainability significantly influence property value dynamics. In addition, the quality of construction implementation, technology selection, and project risk management are also key elements that affect the success of regional development. This identification provides strategic insights for construction managers, property developers, and policymakers in designing and executing projects supporting urban property value enhancement. Thus, this inquiry contributes to improving high-value, resilient, and sustainable areas by the principles of construction management and sustainable development goals.